Exploration of Understorey Vegetation's Beauty: Supporting Tourism Potential of Bukit Siguntang, Palembang - Auliandari, Lia; Lensari, Delfy; Angraini, Erni (Graduate School, Universitas Brawijaya, 2019)
Bukit Siguntang Forest, an urban forest on a hill filled by trees that are believed to be a tomb complex of Malay kings. As an ecosystem, Bukit Siguntang Forest also consists of various understorey. Because of the tourist location, the understorey of Bukit Siguntang Forest tends to be easier to encounter cleaning which is considered as weed and disturbs beauty. The study purpose was to explore the aesthetic potential of the understorey vegetation of Bukit Siguntang Forest. The study method used vegetation analysis with the plot measuring 2m x 2m, which was followed by species identification. The results showed that the understorey identified as dominating species with aesthetic potential were Asystasia gangetica, Bidens pilosa, Borreria laevis, Drymaria cordata, and Mimosa pudica. The understorey which is included in herbs and shrubs had beautiful flowers, unique leaf shapes, and attractive colors. These plants provide the beauty of their parts so that they can be applied to form a flower bed, green coverage and refreshing scenery. However, the growth of understorey also needs to be controlled. That is because understorey can grow rapidly, so that will be growing too densely and messy planting mode.Keywords: aesthetic function, Bukit Siguntang, tourism, understorey vegetation.